2022
DOI: 10.1038/s41598-022-14158-1
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin ameliorated low dose-Bisphenol A induced gastric toxicity in adult albino rats

Abstract: Bisphenol A (BPA) is one of the most common worldwide chemicals involved in the industry of polycarbonate plastics, medical devices, and pharmaceuticals. Forty three-month-old albino rats were randomly classified into four groups. Group Ӏ received a daily corn oil dose (5 mL/kg/ body weight, BW) through a gastric tube for one month, Group ӀӀ received a daily dose of Curcumin (200 mg/kg body weight (B.W.) through a gastric tube for one month, Group ӀӀӀ received a daily dose of BPA (0.5 μg/kg B.W.) through a gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Our data revealed that BPA administration induced histopathological changes in the gastric structure indicated by congestion of vasculature and edema at submucosal layer of the non-glandular layer of the stomach, and congestion of the blood vessels at the mucosal layer of the glandular part. These results are in agreement with Ismail and El-Meligy [18] who mentioned that administration of BPA to male albino rats resulted in dilated congested blood vessels and submucosal edema at the glandular part of the stomach. It has been stated that edema with BPA administration may be related to the release of histamine following gastric damage which led to vasodilatation and an increase in the capillary permeability, and intestinal fluid [19].…”
Section: Discussionsupporting
confidence: 92%
“…Our data revealed that BPA administration induced histopathological changes in the gastric structure indicated by congestion of vasculature and edema at submucosal layer of the non-glandular layer of the stomach, and congestion of the blood vessels at the mucosal layer of the glandular part. These results are in agreement with Ismail and El-Meligy [18] who mentioned that administration of BPA to male albino rats resulted in dilated congested blood vessels and submucosal edema at the glandular part of the stomach. It has been stated that edema with BPA administration may be related to the release of histamine following gastric damage which led to vasodilatation and an increase in the capillary permeability, and intestinal fluid [19].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the effects of Se deficiency on the digestive system are mainly characterized by an increase in apoptosis and pyroptosis ( Wang et al, 2022 ; Shi et al, 2023 ). As one of the important components of the chicken digestive system, the muscular stomach grinds food for further digestion in the glandular stomach and is a key target for Se deficiency and exposure to toxicants ( Gao et al, 2016 ; Sharma et al, 2021 ; Ismail and El-Meligy, 2022 ). The aim of this study was to investigate the mechanisms of BPA or/and Se deficiency-induced damage to the chicken muscular stomach, and the results of our study showed that BPA or Se deficiency exposure induced inflammatory damage in the muscular stomach, activation of the iNOS/NO pathway and the IL-6/JAK/STAT3 pathway, and pyroptosis and myogenic differentiation disorder.…”
Section: Discussionmentioning
confidence: 99%
“…About 50 mg/kg BPS and 0.5 μg/kg BPA affected pathological changes in body weight, gastrointestinal, lung and renal histology, causing induction of vacuolization of rat gastric wall cells, dilated and congested blood vessels, and submucosal oedema ( Sharma et al, 2021 ; Ismail and El-Meligy, 2022 ). There was significant inflammatory damage in the gastrointestinal tissues of chicks in the low Se group, with the presence of a large number of inflammatory cells between the local muscle fibers ( Gao et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, BPA induces deleterious morphological alterations in enteroendocrine, chief, and parietal cells, along with vascular dilation and congestion. These detrimental effects coincide with diminished Periodic acid-Schiff (PAS)-positive reactivity, heightened collagen fiber deposition, decreased immunoexpression of B-cell lymphoma 2 (BCL2), increased Proliferating cell nuclear antigen (PCNA) immunoexpression, and a reduction in gastric mucosal height [ 31 ]. BPA induced notable histopathological changes in the gastric tissue, marked by vascular congestion within the muscular layer of the glandular region and submucosal edema in the non-glandular portion [ 32 ].…”
Section: Bpa-induced Organ Toxicitymentioning
confidence: 99%